2020
DOI: 10.1002/qua.26220
|View full text |Cite
|
Sign up to set email alerts
|

Rényi and Tsallis entropies of the Dirichlet and Neumann one‐dimensional quantum wells

Abstract: A comparative analysis of the Dirichlet and Neumann boundary conditions (BCs) of the one-dimensional (1D) quantum well extracts similarities and differences of the Rényi R(α) as well as Tsallis T(α) entropies between these two geometries. It is shown, in particular, that for either BC the dependences of the Rényi position components on the parameter α are the same for all orbitals but the lowest Neumann one, for which the corresponding functional R is not influenced by the variation of α. Lower limit α TH of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 53 publications
7
24
0
Order By: Relevance
“…The present research expands the previous 1D endeavor [ 6 ] to the comparative analysis of the influence of the Dirichlet and Neumann BCs on the Rényi and Tsallis entropies of the 2D circular quantum dot. It is revealed that the lowest thresholds of the range, where momentum functionals exist, are not only BC‐dependent, but dimensionality strongly influences them too; namely, the 2D geometry pushes them higher: αTHD=2/5 and αTHN=2/3 where, similar to the 1D well, [ 6 ] Dirichlet value is again smaller than its Neumann counterpart. As αTHN is greater than one half, the Rényi inequality from Equation ) has its upper boundary at α = 2, at which its left‐hand side diverges, whereas for the Dirichlet configuration, the corresponding sum is defined for the whole interval of the uncertainty relation [1/2, +∞).…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…The present research expands the previous 1D endeavor [ 6 ] to the comparative analysis of the influence of the Dirichlet and Neumann BCs on the Rényi and Tsallis entropies of the 2D circular quantum dot. It is revealed that the lowest thresholds of the range, where momentum functionals exist, are not only BC‐dependent, but dimensionality strongly influences them too; namely, the 2D geometry pushes them higher: αTHD=2/5 and αTHN=2/3 where, similar to the 1D well, [ 6 ] Dirichlet value is again smaller than its Neumann counterpart. As αTHN is greater than one half, the Rényi inequality from Equation ) has its upper boundary at α = 2, at which its left‐hand side diverges, whereas for the Dirichlet configuration, the corresponding sum is defined for the whole interval of the uncertainty relation [1/2, +∞).…”
Section: Introductionmentioning
confidence: 67%
“…Contrary to the 1D well, [ 6 ] the dependence of the Rényi position entropy of the Dirichlet disc RρitalicnmD()α=20.5emln0.5ema+ln0.5emπ+11αln0em()0em20em01z0emJm2()jmnzJm+12()jmnα0emitalicdz is a distinct function of each corresponding level, which is exemplified in Figure 5. As it follows from the most general properties, [ 8 ] RρitalicnmD()α monotonically decreases with its argument increasing.…”
Section: Rényi and Tsallis Entropiesmentioning
confidence: 99%
See 3 more Smart Citations